Law Enforcement of Assault Crimes in Boalemo Regency from Legal Certainty Perspective - Syarif Djafar; Fenty Puluhulawa; irlan puluhulawa (Journal of Law, Human Rights, Immigration, and Corrections, 2026)
This study examines law enforcement of assault crimes in Boalemo Regency from the perspective of legal certainty. The issue is important because police crime data from 2022 to 2024 show that assault remains a prominent local crime requiring consistent legal handling and community protection. This research uses empirical legal research with statutory and conceptual approaches. Data were obtained from police crime records, interviews with law enforcement officers and perpetrators, and relevant criminal law literature. The findings show that law enforcement must be assessed through the application of the Criminal Code, classification of assault, investigation procedures, article determination, victim protection, and limits of police discretion. Legal certainty is reflected in consistent reporting, evidence collection, case handling, and submission procedures. The study concludes that assault law enforcement in Boalemo requires accurate application of the applicable Criminal Code and stronger preventive legal education.